Physico-chemical properties as a tool for monitoring marine water quality in selected coastal beaches of Northern Sri Lanka - Shobiya, G.; Sivashanthini, K.; Grøsvik, B.E. (University of Vavuniya, 2022)
Sri Lanka is an island with extending coastal shores and extra valuable resources. Anthropogenic pressures and climate change have made the coastal environment increasingly susceptible. As coastal waters are dynamic and unstable, monitoring water quality parameters is essential. Monitoring of water quality measures of coastal waters plays a vital role in identifying the pollution sources and understanding the variations in water quality. It is helpful for stakeholders in making policies and standards to ensure the current status of the aquatic environment and life in it. A long-term assessment of physical and chemical properties was conducted every month for 18 months, from August 2020 to January 2022, at the coastal shores of Mathagal, Point Pedro, and Charty Beach to understand the current status and Spatio-temporal variations of water quality parameters in the studied locations. The parameters such as air and water temperature, pH, salinity, Dissolved Oxygen (DO), Total Dissolved Solids (TDS), and Electric Conductivity (EC) were measured on-site using the smarTROLL multiparameter handheld equipment. For statistical analysis, Minitab 2019 statistical software was used. Sampling locations significantly affected the spatial variation of DO but not the other studied parameters. The sampling months significantly affected the temporal variation of all assessed water quality parameters. The overall mean values of air and water temperature, pH, salinity, DO, TDS and EC were 29.90±1.43◦C, 31.61±1.60◦C, 8.11±0.13, 32.57±2.90 ppt, 6.85±0.86 mg/dl, 31.84±2.66 ppt and 52969.6±5355.96 µS/cm respectively. From the current study, it can be pointed out that the water quality parameters are influenced by precipitation and seasonal trends.
Keywords: Long-term monitoring; Pollution; Precipitation; Seasonal trends